An iterative method for solving proximal split feasibility problems and fixed point problems - Wongvisarut Khuangsatung (2020)
© 2019, SBMAC - Sociedade Brasileira de Matemática Aplicada e Computacional. The purpose of this research is to introduce a regularized algorithm based on the viscosity method for solving the proximal split feasibility problem and the fixed point problem in Hilbert spaces. A strong convergence result of our proposed algorithm for finding a common solution of the proximal split feasibility problem and the fixed point problem for nonexpansive mappings is established. We also apply our main result to the split feasibility problem, and the fixed point problem of nonexpansive semigroups, respectively. Finally, we give numerical examples for supporting our main result.